ANALYSIS OF ROAD GEOMETRIC DESIGN ON THE 2 KM MAJALENGKA – CIKIJING ROAD SECTION (KASTURI STREET CASE STUDY) - Sevan Alif Maulana; Jody Martin Ginting; Adinda Fajarika (LEADER: Civil Engineering and Architecture Journal, 2024)
Road geometric design is part of road engineering, with a focus on the engineering design of the physical form of the road to realize the basic function of the road. Road geometry design products include horizontal alignment, vertical alignment, and road cross sections. The geometric design of the road takes into account traffic safety and comfort in accordance with the function of the road. Estimated traffic flows include motorized vehicles, bicycles, and pedestrians. Road construction in developing countries aims to connect isolated areas and encourage economic growth through better population mobility. Therefore, the government needs to be encouraged. This key element focuses on achieving a balance between regional development and national security for national development. Without sufficient access, it will be difficult for people to conduct activities with different parties. When planning grade curves to improve road safety, attention is paid to the type of curve, the condition of the ground contour to avoid slopes and rivers, and the average speed of road users, all of which affect the minimum circle radius. The minimum circle radius value is a factor that affects the sharpness of the road's horizontal curve at a later stage, if the minimum radius is used then the curve will be very sharp. Therefore, the required turn value needs to be considered and adjusted to the standard so that the horizontal curve of the road is not too steep for the user.